Hubungan Daya Tarik Influencer dalam Mempromosikan Hotel 1O1 Urban Jakarta Thamrin melalui Instagram dengan Minat Menginap Konsumen - Marshanda Marshanda; M. Jamiluddin Ritonga (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
Social media has encouraged the use of influencers as a digital marketing communication strategy in the hospitality industry. This study examines the relationship between influencer attractiveness in promoting Hotel 1O1 Urban Jakarta Thamrin through Instagram and consumers' intention to stay. A quantitative survey was conducted involving 200 consumers who had viewed influencer promotional content. Data were collected using questionnaires and analyzed through descriptive analysis and the Spearman Rank Correlation test. The findings reveal a significant relationship between influencer attractiveness and consumers' intention to stay (Sig. = 0.000; r = 0.589), indicating a moderate correlation. The results suggest that higher influencer attractiveness is associated with stronger consumers' intention to stay at hotel 1O1 Urban Jakarta Thamrin. The study recommends improving influencer selection based on the target audience and brand image, while future research should include additional variables to provide a broader understanding of influencer marketing effectiveness in the hospitality industry.